A Primary Report On Acquired Spinal Deformities In School Children (Journal of Namibian Studies : History Politics Culture, 2022)
The purpose of the study was to early identify acquired deformities scoliosis and kyphosis by school screening which permits the more progressing curves to be treated by physical therapy and prevent its progression. Also, to provide valuable data regarding the prevalence and the natural history of acquired deformities. Two hundred and seventy children (from the 4th prep school) contributed in this study. postural assessment for every student was performed by using Plumb line and Adams forward-bending test. The result of this study revealed that about 15% of the total students were affected with spinal deformity. About 25% of the total affected student had scoliosis and 75% of them had kyphosis.